AN ANALYSIS OF NEEDS HIERARCHY IN T HE CHRONICLES OF NARNIA: PRINCE CASPIAN NOVEL (A PSYCHOANALYSIS BY ABRAHAM MASLOW) (EUFONI: Journal of Language, Literary, and Cultural Studies, 2018)
ABSTRACT This research describes the analysis of Abraham Maslow’s Needs Hierarchy of P e t e r P e v e n s i e which are found in The Chronicles of Narnia : Prince Caspian written by C. S. Lewis. The theory of needs by Abraham Maslow is used as the support to the analysis. All findings from the novel are about the characters’ physiological needs, security and safety needs, love and belongingness needs, esteem needs, and self - actualization needs , answer the research’s questions. The research method and approach is qualitative. Main purpose of this research is to find out the kind of needs that the character own which are potrayed in the novel. The result of the study shows that the character experiences all of kinds of needs in the hierarchy, even reaches the highest level of need. Key words: needs, hierarchy, self actualizatio